Factors influencing corporate governance in Ukrainian companies - Afanasieva, Larysa (Видавництво Львівської політехніки, 2013)
The factors influencing corporate governance in Ukraine have been identified. As a result of the conducted analysis and case studies the essence of each have been revealed. The specificity of Ukrainian corporate governance system have been described. The importance of corporate collaboration within different authority levels have been underlined and the necessity of Ukrainian companies’ adaptation to internationally unified rules, principles and standards of corporate governance have been highlighted. The ways of Ukrainian corporate governance improvement have been pointed out.
Keywords: corporate sector of economy; corporate governance; factors of influence; structural transformation; state regulation; improvements; internationalization process; corporate governance standards; process of institution building; human capital asset